2013
DOI: 10.22456/1807-9806.40831
|View full text |Cite
|
Sign up to set email alerts
|

Composição isotópica de Sr, C e O e geoquímica de ETR das rochas carbonáticas do Bloco São Gabriel, Rio Grande do Sul

Abstract: O Bloco São Gabriel, localizado na zona central do embasamento cristalino do Rio Grande Sul, apresenta extensos registros do Neoproterozóico do Ciclo Brasiliano, contidos em complexos ígneos e metamórficos. Esses complexos também guardam registros sedimentares, com sequências carbonáticas metamorfisadas, cuja evolução tectônica é pouco conhecida. Por essa razão, buscou-se nesse trabalho investigar a origem e a evolução das rochas carbonáticas ocorrentes no Bloco São Gabriel por meio da caracterização geoquímic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 22 publications
2
0
0
Order By: Relevance
“…560 Ma (Remus et al, 2000a) reveled values of 0.7074 ( 87 Sr/ 86 Sr), -0,26‰ and 2.44‰ (δ 13 C PDB ) and -5.68‰ (δ 18 O PDB ) (Passo Feio) 0.7069 ( 87 Sr/ 86 Sr), 5.75‰ (δ13CPDB) and -11,64‰ (δ18OPDB) (Cambai Complex). These data confirmed depositional age of 770 -730 Ma to Passo Feio Formation and 740 -730 Ma to Cambai Complex (Goulart et al, 2013).…”
Section: Sr/ 86 Srsupporting
confidence: 78%
“…560 Ma (Remus et al, 2000a) reveled values of 0.7074 ( 87 Sr/ 86 Sr), -0,26‰ and 2.44‰ (δ 13 C PDB ) and -5.68‰ (δ 18 O PDB ) (Passo Feio) 0.7069 ( 87 Sr/ 86 Sr), 5.75‰ (δ13CPDB) and -11,64‰ (δ18OPDB) (Cambai Complex). These data confirmed depositional age of 770 -730 Ma to Passo Feio Formation and 740 -730 Ma to Cambai Complex (Goulart et al, 2013).…”
Section: Sr/ 86 Srsupporting
confidence: 78%
“…In the newly-formed arc coast, the deposition of carbonate sediments associated with marls and pelites occurred, which generates marbles and pelitic schists, interpreted by the cited authors as deposited in a restricted ocean environment (Goulart et al 2013), in accordance with the proposed model. Goulart et al (2013) also dated the marbles found in the PFMC through Sr 87 /Sr 86 and stable isotopes, obtaining a carbonate sediment deposition age between 770 and 730 Ma, which serves as an indirect dating of approximately 760 to 740 Ma for the crystallization age of the studied metabasites, given the lack of an absolute crystallization age dating of these rocks (Fig. 14C).…”
Section: Evolution Modelsupporting
confidence: 66%